Efficacy and effectiveness of recombinant human activated protein C in severe sepsis of adults - Schumacher, Helge Knut (German Medical Science GMS Publishing House, 2007)
INTRODUCTION: Sepsis is defined as an invasion of microorganisms and/or their toxins into the blood associated the reaction of the organism to this invasion. Severe sepsis is a major cost driver in intensive care medicine. In Germany, prevalence data was assessed in the context of the German Prevalence Study. Severe sepsis has a prevalence of 35% in German intensive care units. RESEARCH QUESTIONS: The following questions were analysed: is Drotrecogin alfa (activated) (DAA) effective in the treatment of patients with severe sepsis and a mixed risk of death, both in all patients and in different subgroups? Is DAA effective in the treatment of patients with severe sepsis and low risk of death? Is DAA cost effective in the treatment of patients with severe sepsis compared to placebo? METHODS: Only studies with adult patients are included. There are no other exclusion criteria. A systematic literature search is performed by the German Institute of Medical Documentation and Information (DIMDI). The literature search yielded as a total of 847 hits. After screening of the abstracts, 165 medical and 101 economic publications were chosen for full text appraisal. RESULTS: Therapy with DAA appears to be cost effective in reducing 28-day-mortality in patients with severe sepsis and a high risk of death. A high risk of death is indicated by the presence of multiorgan failure (≥2) and/or an APACHE-II-Score ≥25. Therapy with DAA is not associated with a long-term reduction of mortality at later follow-up assessments. Therapy with DAA is not associated with a long-term reduction of mortality at later follow-up assessments. Therapy with DAA is cost-effective in patients with multiorgan failure and/or an APACHE II Score (≥25). In patients with a lower risk of death, DAA is not cost-effective. Costs associated with bleeding events have been rarely included in cost calculations. DISCUSSION: DAA appears to reduce mortality in patients with severe sepsis and a high risk of death, but not in patients with a low risk of death. Bleeding events and mortality are considerable higher in studies in the usual care setting compared to clinical trials. In a number of subgroup analyses, both retrospectively and prospectively performed, DAA was not significantly associated with improved survival. The role of concurrent therapy with heparin is unclear, as DAA was only effective in reducing mortality in patients without heparin. There was no significant long-term survival benefit associated with DAA beyond the initial 28 days. Also, there is a lack of studies assessing prospectively functional ability, health-related quality of life, and morbidity in the long-term. In the subgroup of patients with a high risk of death, therapy with DAA ranges at the top level of generally accepted costs per LYG or QALY, in the subgroup of patients with low risk of death, cost effectiveness ratios were higher than those accepted for resource allocation. CONCLUSION: Due to the lack of effectiveness of DAA in patients with severe sepsis and a low risk of death as well as with regard to the high bleeding rates in the usual care setting, indication for DAA therapy. In those subgroups with no significant survival benefit, prospective studies with adequate sample size are needed. With regard to the heterogeneity of severe sepsis, comorbidity and concurrent medication have to be taken into account in further studies. Studies with alternative study designs, for example studies comparing heparin alone or in combination with DAA to placebo, as well as studies conducted by different researchers are needed. Costs induced by bleeding events should also be taken into account in future studies, as bleeding events are the major complica-tion associated the DAA therapy.